Cultivation of Scenedesmus dimorphus with air contaminants from a pig confinement building. (15th July 2022) - Uguz, Seyit; Anderson, Gary; Yang, Xufei; Simsek, Ercan; Osabutey, Augustina
Abstract: The continual consolidation and concentration of animal feeding operations (AFOs) raises various environmental challenges, including air pollutant emission. Cost-effective mitigation technologies are pursued to protect the health and wellbeing of animals and farmers as well as the environment. Previous lab studies utilized ammonia (NH3 ) and carbon dioxide (CO2 ), two major air pollutants in AFOs, for microalgal cultivation. However, the field performance of this algae-based mitigation approach has yet to be investigated. In this study, two photobioreactors (PBRs) were tested in a nursery pig barn to mitigate NH3 and CO2 while growing Scenedesmus dimorphus ( S. dimorphus ). Pit air was fed into the PBRs where the two pollutants were adsorbed by S. dimorphus as nutrients to produce algal biomass and oxygen gas (O2 ). The cleaned air then recirculated back to the room space. S. dimorphus reached its maximum cell count on the 17th day of the experiment when NH3 and CO2 concentrations in the pit air were 25.6 ppm and 3150 ppm, respectively. The maximum biomass concentration occurred on the 11th day when the NH3 and CO2 concentrations were 14.6 and 2250 ppm, respectively. The average mitigation efficiency was 31–50% for NH3 and 1–1.7% for CO2 . The costs for removing 1 g NH3 and CO2 were estimated to be 3.77 and 0.20, respectively. This study shows that an integrated PBR system is technically feasible for reducing pig barn air pollutant emission while producing microalgae as a valuable product. Graphical abstract: Image 1 Highlights: Scenedesmus Dimorphus was cultivated with the pit air in a pig barn. ∼31–50% NH3 and 1–1.7% CO2 were captured and converted into algal biomass. Even with incoming NH3, the medium pH stayed 6.8–7.0 requiring minor adjustment. The highest cell count and algal biomass were 14.9 x 10 6 cells mL −1 and 0.892 g L −1